2014
DOI: 10.2478/cerce-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Growth in Control and Primed Seeds of Pepper as Affected by Salt Stress

Abstract: ABSTRACT. Salinity is an important abiotic stress which can affect crop production in the world. One of the simplest methods for improving salinity tolerance of plants is seeds priming. This experiment was conducted to evaluate the effects of seeds priming with three solutions (KCl , NaCl and CaCl 2 ) in germination and later growth of three pepper (Capsicum annuum L.) cultivars: Beldi, Baklouti and Anaheim Chili. Seeds germination was conducted in a completely randomized design under seven salinity levels (0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…(Kaya et al, 2006). The radicle and stem length of pepper were reduced by increased salinity levels, and plants derived from primed seeds developed a longer radicle and stem for all salinity levels and for all cultivars (Aloui et al, 2014). These results are in accordance with Liu et al (1996), who reported that osmotic priming can improve radical and plumule length in primed tomato seeds.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…(Kaya et al, 2006). The radicle and stem length of pepper were reduced by increased salinity levels, and plants derived from primed seeds developed a longer radicle and stem for all salinity levels and for all cultivars (Aloui et al, 2014). These results are in accordance with Liu et al (1996), who reported that osmotic priming can improve radical and plumule length in primed tomato seeds.…”
Section: Discussionsupporting
confidence: 81%
“…But, Addition of CaCl 2 along with NaCl could completely ameliorate the inhibitory effect of NaCl. Additionally, the proline content of priming pepper (Capsicum annuum L.) seeds with CaCl 2 caused a marked increase under salt stress (Aloui et al, 2014). The crops planted in the soda saline-alkali soil can reduce their yields.…”
Section: Discussionmentioning
confidence: 99%
“…Melon seeds primed with 18 dSm -1 NaCl solution for 3 days at 20°C prior to sowing increased their seedling growth evidences such that, seed priming prior to sowing improves melon physiological performance. Likewise, seed priming with NaCl induce possible physiological adjustments in pepper seeds and Dekoko seeds, especially in the early stages of development which could be used as a suitable tool for improving germination and growth physiognomies of crops under salt stress conditions (Sivritepe et al, 2003;Aloui et al, 2014;Tsegay and Gebreslassie, 2014) and potassium priming and genetic engineering, which serve as a means to improve plant resistance to salt stress (Cushman and Bohnert, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds need about 24 h to general soak and pre-germinate with temperature controlled at about 25°C. Studies have shown that seed soaking with a certain concentration of salt solutions such as KCl, NaCl, or CaCl 2 is beneficial to rice germination [99][100][101][102][103] . Drying can improve the seed germination rate by more than 20% and reduce the germination time to 1-3 days [16] .…”
Section: Rice Seed Treatmentmentioning
confidence: 99%